Literacy teachers' critical pedagogy training and their development of a literature module - Calang, Jubilee Joy S. (College of Education, University of the Philippines Diliman, 2021)
"Using literature with a critical pedagogy lens has lent itself well to teaching for social critique and action. However, this has not been as widely explored in the Philippines context, particularly in the primary grades. This study was grounded on the premise that as much as teachers are called upon to use literature critically with their students, they should be provided the space and support for the undertaking. This qualitative multiple case study used critical discourse analysis to examine three K-1 literacy teachers' starting notions of critical pedagogy in the context of literature use. It also examined the design of the training program that the teachers co-created within a professional learning community (PLC). Moreover, it investigated the impact of the co-created training program on the teachers' notions of critical pedagogy and on their development of a literature module. Findings revealed that the teachers had notions that were consistent with critical pedagogy in some respects and counter to it in others. Their co-created training program was resonant with the commonly used instrumental design, with communicative design elements of group deliberation and consensus. This program mostly added to the teachers' existing notions of critical pedagogy. It also led them to retain some and change a few of their prior understandings. Furthermore, it helped address a few of their counter-notions of critical pedagogy. The training program also provided opportunities for applying critical pedagogy principles in the teachers' development of a literature module. These findings suggest that deliberate efforts are needed to support teachers in taking up critical pedagogy in their use of literature. Program co-creation is also an initiative that benefits teachers as it allows them to have possession over their continuing professional development." --